A Hospital Management Strategies for Advancing Digital Innovation in Human Resources - Azmii Lathifah; Betharia Efriani; Gita Rahayu; Muhhamad Ridho Sahputra (Advantage: Journal of Management and Business, 2026)
The increasing demand for digital transformation in the healthcare sector requires the readiness of human resources (HR) as a key determinant of innovation success. However, in practice, HR still faces challenges such as limited infrastructure, low digital literacy, resistance to change, and data security issues, which affect hospital competitiveness and sustainability. This study examines hospital management strategies in fostering digital innovation in HR. Using a descriptive qualitative approach, this study employs a narrative review, synthesising relevant scientific literature, which is then analysed using thematic analysis. The findings indicate that effective strategies focus on implementing Digital Human Resource Management (DHRM), strengthening digital competencies through continuous learning, and supporting transformational leadership and an adaptive organisational culture. The results also suggest that the success of digital HR innovation is largely determined by the holistic integration of technology, human capabilities, and organisational governance. These findings imply that hospitals need to adopt integrated and strategic HR management approaches to support sustainable digital transformation. This study contributes conceptually by developing a digital-based HR management strategy framework and practically by providing a reference for hospitals in designing sustainable digital transformation policies.